Peripheral Bone Removal versus Sequential Drilling Protocol in Dental Implant Surgery: A 5-Year Retrospective Study - Alhamdani, Faaiz Yaqub; Hassan, Ahmad Fliah; Hussein, Hashim Mueen (European Journal of Dentistry, 2023)
Objective The aim of this study was to compare the immediate success rate between peripheral bone removal (PBR) and conventional sequential drilling protocols.Materials and Methods Biographic data of 130 Iraqi patients who attended a private dental implant center in Baghdad between January 7, 2018 and February 30, 2023 were collected. During this period, 198 dental implant procedures were completed. The recorded data included the zone of implantation, immediate or delayed implant, sinus lift procedure, dental implant system, bone augmentation, and dental implant length and diameter.Statistical Analysis SPSS Ver. 25 was used for statistical analysis. Both descriptive and inferential statistics were applied.Results In total, 198 dental implant procedures were performed during the study period. Of these, 104 cases were treated with the PBR protocol and 94 with the conventional drilling protocol. Out of 130 patients included in this study, 70 were treated with the PBR (IBS) technique and 60 patients were treated with the conventional dental implant systems. The early success of osseointegration reported in this study for all of the cases exceeded 93%. The PBR protocol was successful in 96 cases (92.3%), whereas early success of osseointegration in patients treated with the conventional protocol was reported in 89 cases (94.7%). The chi-squared test showed no statistically significant difference in the early success rate between the two dental implant protocols (p = 0.575).Conclusion In terms of immediate success, the PBR technique appears to be a reliable drilling technique. However, further longitudinal studies need to explore its potential to replace the sequential drilling protocol.
Keywords: oral surgery; dental implant; sequential drilling; peripheral bone removal protocol